Diversidade genômica de isolados nosocomiais de pseudomonas aeruginosa multidroga resistentes - Alves, Stephanie de Almeida (2020)
Pseudomonas aeruginosa is an opportunistic and multi-drug resistant bacillus commonly involved in infections related to healthcare assistance. This study aimed to investigate the antimicrobial susceptibility profile of nosocomial strains of P. aeruginosa isolated from inpatients of a teaching hospital in the City of Sobral, Ceará, Brazil (Santa Casa de Misericórdia de Sobral) from March/2019 to March/2020, as well as to assess the occurrence of resistance genes bla-TEM like, bla-SHV like, bla-CTX-M 1/2, bla-IMP-1, bla-KPC like, bla-GES like, blaSPM-1, bla- NDM-1, bla-VIM like. Bacterial identification and antimicrobial susceptibility tests (AST) were performed using the automated system Vitek®2. Conventional polymerase chain reaction (PCR) assays were used to amplify genes of interest. Thirty-eight specimens of P. aeruginosa were collected and subjected to AST, and thirty-one isolates were subjected to molecular biology analysis. High resistance rates to cephalosporin and tigecycline and low resistance rates to Imipenem and Meropenem were observed, whereas mostly isolates were sensible to colistin. Among the ESBL-coding genes, bla-CTX-M 1/2 prevailed the most (41.9%), while bla-GES like was highly identified among the carbapenemase-producing strains (12.9%). The genes bla-SPM-1, bla-NDM-1, and bla-VIM were not detected. The results demonstrated considerable resistance rates to beta-lactam antibiotics, which could be attributable to the indiscriminate use of antibiotics in the analyzed hospital, whose control essentially relies on the improvement of antimicrobial prescription policies. Furthermore, the prevalence of bla-CTX-M 1/2 genes suggests that these enzymes are the major ESBL responsible for the beta-lactam resistance phenotypes among the analyzed strains.